Lack of avidity maturation of merozoite antigen-specific antibodies with increasing exposure to Plasmodium falciparum amongst children and adults exposed to endemic malaria in Kenya. - Frances Ibison; Ally Olotu; Daniel M Muema; Jedida Mwacharo; Eric Ohuma; Domtila Kimani; Kevin Marsh; Philip Bejon; Francis M Ndungu (PLoS ONE)
Background Although antibodies are critical for immunity to malaria, their functional attributes that determine protection remain unclear. We tested for associations between antibody avidities to Plasmodium falciparum (Pf) antigens and age, asymptomatic parasitaemia, malaria exposure index (a distance weighted local malaria prevalence) and immunity to febrile malaria during 10-months of prospective follow up. Methods Cross-sectional antibody levels and avidities to Apical Membrane Antigen 1 (AMA1), Merozoite Surface Protein 1(42) (MSP1) and Merozoite Surface Protein 3 (MSP3) were measured by Enzyme Linked Immunosorbent Assay in 275 children, who had experienced at least one episode of clinical malaria by the time of this study, as determined by active weekly surveillance. Results Antibody levels to AMA1, MSP1 and MSP3 increased with age. Anti-AMA1 and MSP1 antibody avidities were (respectively) positively and negatively associated with age, while anti-MSP3 antibody avidities did not change. Antibody levels to all three antigens were elevated in the presence of asymptomatic parasitaemia, but their associated avidities were not. Unlike antibody levels, antibody avidities to the three-merozoite antigens did not increase with exposure to Pf malaria. There were no consistent prospective associations between antibody avidities and malaria episodes. Conclusion We found no evidence that antibody avidities to Pf-merozoite antigens are associated with either exposure or immunity to malaria.